Insecticide Resistance in the West Nile Encephalitis, Japanese Encephalitis, Avian Malaria and Lymphatic Elephantiasis Vector, Culex pipiens complex (Diptera: Culicidae) in Iran - Amrollah Azarm; Mohammad Nasrabadi; Fatemeh Shahidi; Awat Dehghan; Fateme Nikpoor; Alireza Zahraie-Ramazani; Seyede Maryam Molaeezadeh; Faramarz Bozorgomid; Ghazal Tashakori; Hassan Vatandoost (Tehran University of Medical Sciences, 2022)
Background: Culex pipiens complex is considered as a vector of some important diseases suchas West Nile fever, equine encephalitis, Rift valley fever, St. Louis encephalitis, Elephanthiasis and avian malaria in the world. The main measure for vector control is using insecticides. High use of insecticides caused resistance in the populations. The aim of this study was to review the status of insecticide resistance in the vector. Methods: Insecticide resistance in this species was found by the available papers and map of the data for carbamates, organochlorine, organophosphates, pyrethroids, microbial and insect growth regulator insecticides were done. An intensive search of scientific literature was done in "PubMed", "Web of Knowledge", "Scopus", "Google Scholar", "SID", and related resources. Results: Results showed that a wide variety of resistance to different insecticides in the country. Due to importance of this species in transmission of diseases. Discussion: resistance management strategies should be further considered to prevent from in secticide resistance and replacement of novel approach for vector control.